ANALISIS PERBANDINGAN METODE MANAJEMEN PROYEK TI YANG PALING SERING DIGUNAKAN DI INDONESIA DAN LUAR NEGERI: A LITERATURE REVIEW - Afifa Witania; Ardina Dana Nugraha; Ermawati Ermawati; Luluk Fajar Sari; Nikita Lia Megawati; Nuzul Nur Fadillah (Journal of Management Small and Medium Enterprises (SMEs), 2022)
In order to achieve its goals and objectives, every company needs to choose the most effective IT project management method. This study aims to determine which methods are used by companies the most, in IT project management governance, both domestic and foreign companies. This study also aims to determine which methods are most effectively used. Systematic Literature Review (SLR) is conducted to collect and evaluate previous studies related to IT project management. Among studies collected from DOAJ and Google Scholar, only 23 studies are considered eligible. This study finds that scrum is both the most used and the most effective IT project management method in domestic companies while agile is both the most used and the most effective IT project management in foreign companies. Keywords: SLR, IT project management, IT project management method